Numerical investigation of steady suction control of flow around a circular cylinder. (November 2015) - Chen, Wen-Li; Cao, Yong; Li, Hui; Hu, Hui
Abstract: This paper numerically investigates the effectiveness of the control of steady suction on a stationary circular cylinder with several isolated suction holes on the surface at a subcritical Reynolds number. The control effectiveness as a function of the azimuthal position, spanwise spacing and suction flow rate of the suction holes on the control of the aerodynamic forces on the cylinder and the suppression of alternate vortex shedding are taken into account. The study of the azimuthal location of the suction holes indicates that azimuthal angles of θ =90° and 270°, which are close to the separation point, provide the most substantial decreases in the aerodynamic forces. When restricted to the most effective azimuthal angle, a remarkable control effectiveness can be achieved when the axial spacing between two neighboring suction holes is less than a minimum value even under a small suction momentum coefficient. However, if the axial spacing exceeds the minimum spacing, the control effectiveness will not be saturated even under a very large suction momentum coefficient. Thus, the cause of the effective aerodynamic force control is suggested to be a result of obvious three-dimensional phenomenon in the near wake, which is characterized by the generation of a convergent flow between two neighboring suction hole sections and a stronger, larger three-dimensional vortex pair adjacent to the convergent flow. It has been suggested that this strongly three-dimensional flow pattern is induced by the strong interaction between two neighboring but counter-rotating three-dimensional vortices separately produced by two neighboring suction holes. Moreover, the effects of such three-dimensional flow patterns are investigated in detail based on variations in the flow field and sectional aerodynamic forces in different cross sections. Finally, the upper limit of the axial spacing between two neighboring suction holes to form such a three-dimensional flow pattern is suggested to be between 0.75 D and 1.5 D when the suction flow rate exceeds a certain value.